2009
DOI: 10.1007/s11105-009-0091-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Organellar and Cytosolic AtHSP90 in Arabidopsis thaliana Impairs Plant Tolerance to Oxidative Stress

Abstract: Three AtHSP90 isoforms, cytosol-localized AtHSP90.2, chloroplast-localized AtHSP90.5, and endoplasmic reticulum (ER)-localized AtHSP90.7 genes, were constitutively overexpressed in Arabidopsis thaliana to study their functional mechanisms under oxidative stress. Overexpression of AtHSP90 genes reduced germination of transgenic seeds under oxidative stress. When exposed to 10 mM H 2 O 2 , AtHSP90 transgenic seedlings displayed lower activities of superoxide dismutase, catalase, and peroxidase; higher content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 31 publications
(31 reference statements)
1
22
0
2
Order By: Relevance
“…Overexpression of Hsp90C in Arabidopsis reduces tolerance to salt, drought, and oxidative stress (43,44). Additionally, the cr88 mutant, a Gly-to-Arg substitution at position 646 of Hsp90C in Arabidopsis, alters responses to red light and constitutively delays chloroplast development (18).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Hsp90C in Arabidopsis reduces tolerance to salt, drought, and oxidative stress (43,44). Additionally, the cr88 mutant, a Gly-to-Arg substitution at position 646 of Hsp90C in Arabidopsis, alters responses to red light and constitutively delays chloroplast development (18).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have been implicated in both signaling and triggering of PCD (Burbridge et al 2006;George and Parida 2010;Song et al 2009). Hydrogen peroxide (H 2 O 2 ) generated by various environmental and developmental stimuli can act as a signaling molecule that regulates plant development, stress adaptation, and PCD (Apel and Hirt 2004;Gao et al 2010).…”
Section: Ospdcd5-induced Cell Death Exhibited Multiple Pcd Featuresmentioning
confidence: 99%
“…Previous studies revealed that the Hsp90 gene not only is induced by abiotic stresses such as saline-alkaline, high temperatures, low temperatures, and heavy metals (Pareek et al, 1995;Song et al, 2009), but also is involved in the plants' resistance to pathogens. Wang et al (2011) found that wheat plants over-expressing the Hsp90 gene family members TaHsp90.2 and TaHsp90.3 showed significant resistance to stripe rust.…”
Section: Introductionmentioning
confidence: 99%